The Effect of Speed, Agility and Quickness (SAQ) Training on Developing the Effective Movement of Tennis Players - Ali, Sura Mahmoud (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: The aims of the study were the preparation of Speed, Agility and Quickness (SAQ) training on developing the effective movement of tennis players, and identify the effect of Speed, Agility and Quickness (SAQ) training on developing the effective movement of tennis players. Design: an experimental design was used. Setting: the subjects were randomly divided into two groups; the control group and the experimental group received SAQ training for50-60 minutes. Participants: Twenty four participants were chosen from Iraqi Tennis Federation Players and their mean age 19.86 ± 1.81 years. Main Measures: Pre- and post-tests included: Planned Agility test. Results: there were significant differences between the experimental group Speed, Agility and Quickness (SAQ) training and control group in the agility planned test. Conclusions: showed that the Speed, Agility and Quickness (SAQ) training was more effective training on developing the effective movement for tennis players.